PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN ASING TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA SEKTOR KEUANGAN DI BURSA EFEK INDONESIA - Ahzan, Andi Amal; Alamsjah, Alamsjah; Nasrullah, Nasrullah (LPPM - STIE SAKTI ALAM KERINCI, 2025)
This research aims to see the effect of managerial ownership, institutional ownership and foreign ownership on corporate financial performance in the financial sektor of the Indonesia Stock Exchange for the 2021-2023 period. This type of research is quantitative research. In this research, the data source used is secondary data. The sampling technique in this study used purposive sampling. Samples that meet the criteria are 102 samples. The data analysis method used in this study is multiple regression analysis using the SPSS 30 statistical tool. The result of this study partially indicates that the managerial ownwership has a significant positive effect and foreign ownership has a significant positive effect on financial performance, while institutional ownership has no signifficant effect on financial performance.